Fiscal Policy and the Dynamic Inconsistency of Social Security Forecasts - Aaron, Henry J.; Burtless, Gary (American Economic Review, 1989)
Most economists believe that legislation obligating the government to increase expenditures in the future will have some current stimulative effect on private spending; tax increases scheduled to take place in the future will depress current spending. Few economists, however, have considered the effects of budgeting or actuarial rules that oblige the government to change current spending patterns or tax laws. If such rules are followed, future taxes and expenditures will turn out to be different from current ones. Will private behavior be affected solely by currently legislated tax rates and expenditures? Or will it be affected instead by the taxes and expenditures that current budgeting rules appear to require? This question is central to interpreting the fiscal implications of additions to Social Security reserves. Social Security revenues, including interest, will exceed expenditures by $52 billion in 1989. The annual surplus will reach $98 billion by 1994 and $450 billion by 2020. These shortand medium-term surpluses are projected to be dwarfed by even larger deficits starting around 2030. Using a 2 percent real interest rate and other detailed economic and demographic assumptions, the Social Security actuary now projects that expenditures will exceed revenues over the next 75 years by just under 5 percent of the present discounted value of expenditures. Furthermore, the long-run deficit, measured in present-value terms, will grow larger each year. As each year passes, one year of surplus passes into history and all the future years with large deficits move one year closer. The present value of future benefit obligations will consequently grow relative to the present value of future revenues. Ironically, the annual surpluses in the Social Security accounts will swell to unprecedented levels just as the long-run deficit is rising. Which is the better guide to the effect of Social Security on aggregate demand-the annual surpluses, whose growth suggests that Social Security's contribution to fiscal policy is now restrictive; or the long-term deficits, which are also growing larger and suggest that Social Security is stimulative? One's answer to this question determines one's interpretation of recent budget policy. Consider the effect of the Social Security Amendments passed in 1983. Because the OASDI program faced severe financing problems in the early 1980s, Congress reduced benefit entitlements and raised Social Security taxes, but delayed full implementatDiscussants: Robert M. Ball, National Academy of Social Insurance; Lawrence H. Thompson, U.S. General Accounting Office; John Hambor, Social Security Administration.